Unsolved problems in CDH follow-up - Valfré, Laura; Conforti, Andrea; Morini, Francesco; Patel, Neil; Bevilacqua, Francesca; Cianci, Maria Chiara; Bagolan, Pietro; Braguglia, Annabella (Frontiers in Pediatrics, 2022)
Patients affected by CDH, surviving neonatal period is endlessly increasing thanks to technological and pharmacological improvements. Conversely, patients, families and caregivers are facing, more and more frequently, “new” complex late comorbidities (including chronic pulmonary and cardiac dysfunctions, neurodevelopmental challenges, and nutritional specific requirements), that often lead to long-term needs, either medical or surgical. Therefore, late morbidity is now focusing most of the attentions. Aim of present paper is to stress some of the most important "unsolved problems" on CDH patients at long-term follow-up.